PARTISIPASI KOMUNITAS SEKOLAH INSPIRASI PEDALAMAN DALAM PELAKSANAAN PENDIDIKAN DI DESA PUCUNG BEDUG KABUPATEN BANJARNEGARA - Andani, Ramona Nur (Fakultas Ilmu Pendidikan, 2019)
AbstrakPenelitian ini bertujuan untuk mendeskripsikan tentang partisipasi komunitas SIP dalam pelaksanaan pendidikan di Desa Pucung Bedug Kabupaten Banjarnegara dan melihat faktor pendukung dan penghambat yang ada. Penelitian ini menggunakan pendekatan penelitian kualitatif deskriptif, dan pemilihan subjek penelitian disini ditentukan berdasarkan pertimbangan masyarakat yang mengetahui informasi yang dibutuhkan oleh peneliti. Objek penelitian ini untuk melihat sejauh mana partisipasi komunitas sekolah inspirasi pedalaman (SIP) dalam pelaksanaan pendidikan di Desa Pucung Bedug Kabupaten Banjarnegara dan melihat faktor pendukung dan penghambat pendidikan yang ada di masyarakat Banjarnegara. Setting penelitian ini di wilayah Banjarnegara. Hasil Penelitian ini yaitu partisipasi komunitas SIP di Desa Pucung Bedug Kabupaten Banjarnegara memiliki bentuk partisipasi non fisik dimana kegiatan yang dilaksanakan berupa Pekan Inspirasi, Kelas Profesi dan Kegiatan Kolaborasi antar komunitas yang bertujuan untuk mengubah pola piker masyarakat Banjarnegara untuk lebih mementingkan tingkat pendidikan mereka. Faktor pendukung dan penghambat partisipasi komunitas sekolah inspirasi pedalaman (SIP) adalah 1) keadaan sosial dan ekonomi (2) tingkat pendidikan orang tua(3) aksesibilitas (4) perhatian dari pemerintah (5) pemerataan pendidikan (6) sumber informasi dan pendanaan.Kata Kunci : Komunitas, PendidikanAbstracThis study attempts to described about the participation of the community gather to sip as board members in the implementation of the education in the village pucung bedug kabupaten banjarnegara and carefully observed your objects by factors in support of and inhibitors of of which there are .Was used in the study the approach of the qualitative study descriptive , and selection of the subject of study here paid up shall be determined based on the consideration community members who know of of the required information by researchers .The object of this research to see the extent to which the participation of school community inspiration the interior of (sip as board members) in the implementation of the education in the village pucung bedug kabupaten banjarnegara and carefully observed your objects by factors in support of and inhibitors of to the education system in the midst of society banjarnegara .A look at a this research in the region of banjarnegara. The result of this research pt pgn promised to supply the participation of the community gather to sip as board members in the village pucung bedug banjarnegara having the form of the participation of non physical where the activities that were undertaken in the form of inspired the appearance of modern week to allow more time , a class of for a profession and collaborative activities community which was first established is intended to transform a pattern piker the community banjarnegara to were more concerned with the level of their education .By factors in support of and inhibitors of the participation of school community inspiration the interior of (sip as board members) is (1) the state of social and economic infrastructure through (2) the education level of parents (3) the accessibility of (4) any attention from the government (5) of even distribution of zis education (6) a source of information and financing of .Keyword : Community, education